EVALUATION OF CONDITION OF THE PULP BY PULSE OXIMETRY. - Dimitar Kosturkov; Tsonko Uzunov; Raia Grozdanova; Viktoria Ivancheva (Peytchinski Publishing, 2015)
Purpose: To conduct pulse oximetry (PO) and electric pulp test (EPT) on intact frontal teeth in clinically healthy patients aged between 18 and 25 years who do not have periodontal disease. Material/Methods: To achieve the aim 1058 teeth of 31 patients were studied. The following inclusion criteria for the study were set: 1. Age - 18-25 years. 2. Clinically healthy patient, who does not have any systemic diseases, do not take any medicine systematically. 3. Intact frontal teeth - without carious lesions, restorations or root canal treatment. 4. Lack of periodontal disease. Research was conducted with a pulse oximeter Contec™ - CMS60D and a custom made probe holder. Results: Average values obtained by pulse oximetry in upper jaw vary between 83% and 85%. In lower jaw - between 82% and 85%. 99% is the maximum and 48% is the minimum registered value. The average value of the measurement of all the teeth is 84%. The average saturation measured on the small finger of the right hand of the patient is 98%. The average value of EPT for all teeth is 4 μA. The maximum measured value is 20 μA, and the minimum - 1 μA. Conclusions: 1. Adequate study of the pulp includes two complementary methods - electric pulp test (evaluation of innervation) and pulse oximetry (assessment of pulp microcirculation). 2. Teeth that are larger in size have larger values of PO and EPT, which is in direct relation to the size of their pulp chamber. 3. The total saturation, measured in the little finger of the right hand is greater than the one of the teeth.